Modelling of killer whale population (ORCINUS ORCA) via the Lefkovitch Matrix Model / Muhammad Fitri Shafiee, Muhammad Hilmi Hanis Shuhadak and Muhammad Afiq Zulkipli - Shafiee, Muhammad Fitri; Shuhadak, Muhammad Hilmi Hanis; Zulkipli, Muhammad Afiq (2023)
Orcas, also known as killer whales, are large marine mammals found in every ocean on the planet. Orcas live in social groups called pods and use vocalizations to communicate and navigate. They have a lifespan of around 30-60 years for males and 50-90 years for females, and they give birth to a single calf after a pregnancy of 15-18 months. The rapidly dwindling population has piqued the interest of the international community, whether it be the environmental professionals or ordinary people. Hence, this study applied the Lefkovitch model which is a mathematical tool used to study population dynamics, and it has been used in the study of killer whale Orcinus Orca populations as well as environmental management. The life cycle of Killer Whale consists of five stages which are baby, yearling, juveniles, mature females and post reproductive. These five stages of the killer whale life cycle were used in constructing the transition matrix for the Lefkovitch matrix model.